Educational Philosophy and Its Relationship to Development Curriculum 2013 - Khaerus Syahidi; Muhammad Sarjan; Joni Rokhmat; Syahrial A; I Gde Mertha; Kurniawan Arizona; Syamsuddin Syamsuddin; Ramdhani Sucilestari (Lembaga Bale Literasi, 2023)
This article is discussing The philosophy of urgency education and its relationship to the development of the 2013 curriculum, in which the 2013 curriculum was based on several views of the educational philosophy and philosophy of Pancasila as Indonesia's ideology. This article is a literature review study that seeks to show the meaning of the role of philosophy as a foundation for 2013 curriculum development, based on the results of research studies, the existence of a scientific method that results from philosophical thinking will increasingly lead to curriculum development goals, the aim of curriculum development is based on the foundation of the flow of educational philosophy, the views of educational philosophy is idealism, perennials, essentialism, and the foundation of the ideology of Pancasila, which increasingly shows the urgency of philosophy for curriculum development so that the philosophy and philosophy of education adopted will affect social life, family life, and in the sphere of education. If there is no philosophy in every life there will be many misconceptions.